Skills and Competencies in Higher Education and Beyond - Lilia Raitskaya; Elena Tikhonova (National Research University Higher School of Economics, 2019)
The editorial focuses on the employability skills and the ways they are reflected in the research field of higher education. The topics related to competencies, abilities, attributes and skills are crucially important as they substantially determine the chances of successful employability for university graduates. The multiple approaches and frameworks covering various kinds of qualifications have been emerging since the 1980s, starting from the 21st century skills to the recent key skills required within education for sustainable development. The UN, European Union, OECD, and other international institutions regularly put forward comprehensive frameworks to address the pressing needs of the transforming economy and society for professionals and specialists ready to face the new challenges. The editorial gives a glimpse of the trends JLE is willingly ready to bring out for our readers in the coming years.